Approaches for Improving Personal Training and Development in the Public Middle Schools of Tiantao School in Nanning - Haiyan Wang; Narongpon Aulpaijidkul (New Horizon of Education, 2026)
This study adopted an exploratory research design to examine personal training and development at Tiantao School in Nanning, aiming to assess its current training status and develop targeted practical improvement strategies. Following Krejcie and Morgan’s sampling criteria, 243 teachers and 98 administrative staff were selected via stratified random sampling, yielding 341 valid samples in total. Questionnaire and expert evaluation data were analyzed through descriptive statistics and the modified Priority Needs Index (PNI). Results showed basic training operates adequately; teacher professional development (PNI=0.027) and leadership development (PNI=0.031) are core optimization priorities. Clear position-based demand gaps exist: teachers rank enhancement of teaching competence (PNI=0.053) as their top developmental need, while administrators prioritize team management skills (PNI=0.071). This study constructed a seven-dimensional differentiated training framework covering excellent teaching case studies, cross-school teaching exchanges, teaching reflection journals, team management practices, classic reading, leadership training, and conflict management capacity building. The framework was validated by three educational management experts, receiving ratings of "Very high" for both appropriateness (M = 4.68) and feasibility (M = 4.64), thereby confirming its practical applicability for institutional improvement at Tiantao School and comparable public junior high schools.